Elasto‐plastic phase‐field model for pullout tests of steel fiber embedded in high‐performance concrete: numerical calibration and experimental validation. Issue 1 (18th November 2019) - Pise, Mangesh; Brands, Dominik; Gebuhr, Gregor; Sarhil, Mohammad; Schröder, Jörg; Anders, Steffen
Abstract: In this paper, the pullout behavior of steel fiber embedded in high‐performance concrete (HPC) is investigated. First, a constitutive framework of elasto‐plastic phase‐field model of fracture is constructed and applied to simulation of pullout tests for different embedded lengths of steel fibers. Thereby, the description of the mechanical behavior the Drucker‐Prager plasticity model is used. The numerical calibration of the above mentioned model is performed by simulating pullout tests and validated by data obtained from experiments. Therefore, the mechanical behavior of high‐performance concrete is studied in experiments.